ANALISIS KONDISI SOSIAL EKONOMI TENAGA KERJA PT. TAMACO GRAHA KRIDA DI DESA UNGKAYA KECAMATAN WITAPONDA KABUPATEN MOROWALI - Huzaemah, Huzaemah (Katalogis, 2020)
This study aims to determine the social conditions in education and health as well as the economic conditions on the income of the oil palm plantation workers of PT. TamacoGrahaKrida. This research was conducted at PT. Tamaco Graha Krida Desa Ungkaya, Witaponda Subdistrict, Morowali Regency from February to May 2020. This research used descriptive analysis method, the sample of respondents was taken using purposive sampling method and calculated using the Slovin formula as many as 76 respondents of oil palm plantation workers PT. TamacoGrahaKrida. Based on the results of research on 76 employees of PT. TamacoGrahaKrida, it is known that workforce education is categorized as good, because 65.78% of respondents have attended 12 years of compulsory education, which is categorized as secondary or moderate education, and education in children is categorized as good because as many as 18.86% have attended college, whereas in the workforce's health, 1.31% of respondents had a history of comorbidities with chronic gastritis and diabetes and were declared unhealthy, while respondents who did not have a history of comorbidities and only had minor complaints were 98.68% and declared healthy, and in this condition. the average income received by the respondents is Rp. 3,247,368 per month and it is said to be good because it is higher than the Minimum Wage (UMK) of Morowali Regency in 2020 amounting to Rp. 2,768,593 / month.